Scenario Modeling of Cross-Border Interactions in Central Asia: A Methodological Approach - Malika Djalilova (Scientific Trends, 2025)
This article presents a hybrid methodological framework for scenario modeling of cross-border interactions in Central Asia, with a focus on the Fergana Valley. The region’s geopolitical complexity—marked by disputed borders, interethnic tensions, and uneven institutional capacities—demands an approach that can account for both structural constraints and behavioral dynamics. Combining SWOT analysis and binary logistic regression, the study identifies key variables that influence the probability of conflict or cooperation among neighboring states. Three scenarios—Escalation, Cooperation, and Inertia—are developed based on empirical data and modeled projections. The results highlight the significance of diplomatic engagement, formal agreements, and third-party mediation in shaping outcomes. This scenario-based approach not only enhances predictive capacities but also provides a strategic tool for early-warning systems and policy planning. The methodology is scalable and applicable to other conflict-prone border regions worldwide.
Keywords: Cross-border cooperation, Central Asia, scenario modeling, SWOT analysis, binary probability model, regional security, Fergana Valley, political forecasting.